Student Knowledge Of Antenatal Care Services For Third-Trimester Pregnant Women - Andi Husna; Dwi Noerjoedianto; Budi Aswin; M. Ridwan; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
Antenatal care (ANC) is a key maternal health service that supports monitoring of maternal and fetal conditions, early detection of complications, health education, and preparation for safe delivery. The third trimester is a critical period because the need for monitoring increases near childbirth. This study aimed to describe the knowledge of public health students regarding ANC services for third-trimester pregnant women. A quantitative descriptive study with a cross-sectional approach was conducted at Universitas Jambi from February to March 2026. A total of 100 public health students were selected using purposive sampling. Data were collected using a validated 17-item questionnaire covering ANC definition, aims and benefits, visit frequency, service components, and danger signs. The instrument showed acceptable reliability with Cronbach's Alpha of 0.724. Data were analyzed using univariate analysis. Most respondents had good knowledge (65.0%), followed by moderate knowledge (31.0%) and poor knowledge (4.0%). The highest correct responses were found in aims and benefits, while the lowest were related to visit frequency. Strengthening technical and applied learning is needed to improve student competence.